Synthesis of (Z)-fluoroallyl azides through aluminium-mediated defluorinative functionalization reactions. Issue 7 (11th February 2015) - Sato, Azusa; Yanai, Hikaru; Suzuki, Daiki; Okada, Midori; Taguchi, Takeo
Graphical abstract: Abstract: The reaction of difluorohomoallyl alcohols with Me2 AlCl in CH2 Cl2 selectively gave ( Z )-fluoroallyl chlorides via SN 2′ type defluorinative chlorination. These chlorides were easily converted to the corresponding ( Z )-fluoroallyl azides by the sequential nucleophilic azidation reaction using NaN3 . Direct defluorinative azidation of the difluorohomoallyl alcohols was also achieved by treating with Me3 SiN3 in the presence of Al(O i -Pr)3 . Fluoroallyl azides thus obtained successfully applied to the Huisgen 1, 3-dipolar cycloaddition chemistry.